Conjetura y demostración en el aula en la formación de docentes (2021)
This research work shows how the processes of conjecture and mathematical demonstration in the framework of problem solving favor the development of mathematical thinking manifested by students of the Bachelor of Basic Education with an emphasis on Mathematics of the Santo Tomás University, in the modality from distance. The methodology of this research was qualitative in nature, through case studies of the participants, and was developed under the parameters of the didactic engineering of Michèle Artigue. The theoretical framework is based on the contributions of Gila Hanna (2000) regarding the functionality of the mathematical proof, the contributions of Harel and Sowder (2007) regarding the demonstration schemes developed by the students and the resolution of problems from the Alan Schoenfeld's perspective (1985).